DETERMINATION ANALYSIS OF REGIONAL INCOME TOWARDS DOMESTIC REGIONAL PRODUCT WITH REGIONAL INVESTMENT AS A MODERATOR - Aziz, Khalid; Soeratno; Sri Ambarwati (Dinasti International Journal of Economics, Finance & Accounting, 2020)
Regional income is a source of income for local governments that hold every activity that has an allocation of funds for people. The purpose of this study is to study and analyze the structure of regional income with regional investment as a moderator. This research was conducted at the Regency / City government in West Java Province, this study uses secondary data released from the APBD and PDRB realization report in the period 2014 to 2017. The sample research method used was purposive sampling technique. The analytical method used is the Moderated Regression Analysis using Eviews 9. Based on the results of the analysis obtained from regional original income, regional investment, balanced funds that are moderated by regional investment. Regional original income is moderated by significant regional investment on gross regional domestic product. The results of the study are used to include local governments in managing regional revenue sources and taking an assessment to make regional investments. This journal is the result of his own work and all sources, both quoted and referenced, have been properly approved.